CONTRIBUTION OF FORESTRY SUBSECTOR TO ECONOMIC DEVELOPMENT OF KOTAWARINGIN BARAT REGENCY - Jumri Jumri; Sari Mayawati (TROPICAL WETLAND JOURNAL, 2017)
Forest as the financial capital for development has important roles in economic development of Kotawaringin Barat Regency. Commonly, forest is a large area of land where flora (trees) and fauna (animals) exist. It can produce woods and other products for human consumption (production function), regulate the water system for human life, prevent flooding and sea water intrusion (protection function), and preserve many species of plants and animals and ecosystem (conservation function). Economically, forest as the source of woods, rattans and other products provided foreign exchange for the country during 1980-1990; this case placed the subsector of forestry as one of the prime movers in Indonesia’s economy. The purpose of this research was to analyze the extent of the foresty’s contribution to the economic development and social welfare in Kotawaringin Barat Regency. The research methodology was conducted by: a) interview, b) observation / field surveys and c) documentation (supporting data). The results showed that the contribution of forestry subsector in the economic development and social welfare of Kotawaringin Barat reached IDR 38.6 billion in 2011.